(untitled) (International Journal of Agricultural Research, Innovation and Technology, 2022)
This study was initiated to identify market chain actors and their function in the market, investigate the structure conduct and performance of goat marketing in south omo zones of SNNPR, Ethiopia during the year 2018. Primary data were collected from sampled pastoralists and agro pastoralists, traders and brokers. Before the household survey, key informant interview and focus group discussions were conducted with producers, traders and brokers. Descriptive Statistics and qualitative data analysis techniques were employed to analyze the goat market structure, conduct and performance. The results show that producers, brokers, traders and consumers were the major goat market actors. Regarding the market structure, cattle market is known to be dominated by few traders. Although the degree of competition varies, goat market structure in the study area has an oligopolistic nature. This shows that only few traders have the majority of market share and earn abnormal profit. Besides, goat market is characterized by entry barriers, distant market point, high trucking cost, seasonality of marketing, information asymmetries and unfriendly relation between actors. As the pastoralists and agro pastoralists mainly depend on goat for their livelihoods and other cultural values, traders take advantage of the asymmetric market information towards them. The larger share of the market gains remains with end traders thereby limiting the pastoralists and agro pastoralists chance to realize the economic gains in goat production. Thus, linking producers to market and its benefits, establishing cooperatives and development of infrastructure could play a significant role for optimization of the sector. Int. J. Agril. Res. Innov. Tech. 11(2): 52-60, Dec 2021